Parent–Child Cohesion, Basic Psychological Needs Satisfaction, and Emotional Adaptation in Left-Behind Children in China: An Indirect Effects Model - Shao, Jingjin; Zhang, Lei; Ren, Yining; Xiao, Luxia; Zhang, Qinghua (Frontiers in Psychology, 2018)
This study aimed to validate an indirect effects model of parent–child cohesion in emotional adaptation (i.e., loneliness and depression) via basic psychological needs satisfaction in Chinese left-behind children as well as the applicability of the model to both genders. A cross-sectional study was conducted and included 1,250 children aged between 9 and 12 years (635 left-behind children and 615 non-left-behind children) from rural primary schools. The results showed that: (1) relative to non-left-behind children, left-behind children exhibited significantly higher loneliness and depression scores and greater disadvantages involving father–child cohesion, mother–child cohesion, and psychological needs satisfaction. (2) Father– and mother–child cohesion were significantly negatively correlated with loneliness and depression and significantly positively correlated with psychological needs satisfaction in left-behind children. (3) Through structural equation modeling showed that psychological needs satisfaction partially mediated the relationship between parent–child cohesion and emotional outcomes in left-behind children. (4) Through multi-group analyses showed significant gender differences in structural weighting between parent–child cohesion and emotional adaptation, in that parent–child cohesion in left-behind boys was a stronger negative predictor of unfavorable emotional outcomes relative to that observed in left-behind girls, while psychological needs satisfaction in left-behind girls was a stronger negative predictor of unfavorable emotional outcomes relative to that observed in left-behind boys. The implications of these findings for interventions directed at Chinese left-behind children were discussed.